Non-typhoidal Salmonella in Nigeria: do outcomes of ‘multisectoral’ surveillance, treatment and control justify the intervention costs? - Abdullahi O. Sanni; Abdurrahman H. Jibril; Olubunmi G. Fasanmi; Oluwawemimo O. Adebowale; Alexander R. Jambalang; Aminu Shittu; Annelize Jonker; Latifah O. Abdulkarim; Folorunso O. Fasina (International Journal of Veterinary Science and Medicine)
Non-typhoidal salmonellosis (NTS) is significant and an economic burden in Nigeria. To determine whether investment in NTS control is economically justifiable, Outbreak Costing Tool (OCT) was used to estimate the robust funding of public and animal health systems for epidemio-surveillance and control of multisectoral NTS outbreaks in Nigeria. Health, production, and economic data were collected and used to populate the tool for evaluation. The multisectoral NTS burden for the year 2020 in Nigeria was US$ 930,887,379.00. Approximately 4,835 technical officers, and 3,700 non-technical staff (n = 8,535) were needed with an investment of >2.2 million work hours. The investment cost for NTS control was US$ 53,854,660.87. The non-labour-related cost was 89.21% of the total intervention costs. The overall intervention’s investment was 374.15% of the estimated national and subnational systems’ annual budget for diarrhoeal diseases, and the outbreak response period attracted the highest costs (53%) of the total intervention. In conclusion, intervention against NTS was beneficial (benefit – cost ratio: 17.29), hence justifying the need for multisectoral surveillance-response against NTS in Nigeria. Complex sectoral silos must give way to coordinated collaborations to optimize benefits; and over-centralization of health interventions’ associated delays must be removed through decentralized sub-national-focused framework that empowers rapid investigation, response, control, data collection, and analyses. It should assist anticipatory planning, and outbreak investigation and reduce critical response time. Anticipatory planning tools, when applied pre-emptively, can benefit budgeting, identify gaps, and assist in the delivery of cost-saving and effective measures against infectious disease.